Teens and libraries : getting it right - Walter, Virginia A. (American Library Association, 2003)
Libraries have opportunities to make a positive difference in the lives of teenage customers and become a primary support for teens in the communities they serve. The authors guide both librarians and administrators to make promises for the future and present a strategy for keeping those promises so that young adult audiences can become active library and community participants. From building partnerships to implementing successful programs to incorporating technology that helps teens assume leadership and responsibility, this is an inspiring yet practical take on what it means to "get it right" for teens in the library.